Susceptibility of Enterococcus Faecalis to the Antibacterial Effect of Various Metabolites of the Mammea Americana Seed - Sierra, Donovan Rodríguez-; Miranda, Lizeth Yanes-; Morales A, Eduardo Covo-; Jiménez González, Angie; Caballero, Antonio Díaz- (Jour Med Resh and Health Sci, 2022)
Background: Enterococcus faecalis has been identified as one of the main microorganisms that cause oral infections, especially those of endodontic origin, due to its broad multi-drug-resistant spectrum. Some studies have demonstrated antibacterial activity of Mammea Americana, most of them have focused on extracts obtained from leaves and bark but few indicate an antibacterial activity of plant seeds. Objective: To evaluate antibacterial activity of different metabolites present in Mammea Americana seed extracts against Enterococcus faecalis ATCC (51299). Materials and methods: previously crushed and cold macerated dry plant material was used, employing ethanol as solvent, which was concentrated under reduced pressure and of which four (4) additional organic extracts with solvents of different polarities were obtained. Extracts were solubilized in DMSO and antibacterial activity was measured using the 96-well plates broth microdilution technique in a concentration range of 50 to 500 mg/L, using kanamycin as a positive control and DMSO as a negative control. Results: All evaluated extracts showed inhibitory activity against Enterococcus faecalis. Hexanoic (BMI 100 mg/L) and chloroformic extracts (BMI 200 mg/L) showed higher inhibitory activity. Conclusions: Obtained extracts revealed a variety of secondary metabolites, principally coumarins. All extracts showed inhibitory activity. Hexanoic extracts (BMI 100 mg/L) and chloroformic extracts (BMI 200mg/L) stood out as extracts with the highest activity.